Signs of Aggressive Behaviour in 5-6-year-old Preschool Children - Thi Nhu Mai, Nguyen; Trang, Truong Thu (VNU Journal of Science: Education Research, 2020)
This paper presents the current situation of aggressive behaviours among 5-6-year-old children at several Hanoi's preschools in respect to the opinions of teachers and their parents through surveys, written investigations, interviews and case studies. As preschool children’s aggressive behaviours adversely affect children themselves and those around them, they need to be addressed. The paper shows that the children exhibit aggressiveness through both verbal and nonverbal behaviours, directly or indirectly, but largely through direct nonverbal behaviour aimed at the target; and boys are more likely to exhibit stronger aggressive behaviours but fewer in numbers compared with girls. The research results help clarify the current situation of aggressive behaviours in 5-6-year-old children in Vietnam.